The Effect of Environmental Graphics on the Attractiveness of Museums Interior Architecture - Azarbouyehdinaki, Gholamreza; Eghbali, Parviz; Ghazizadeh, Khashayar (Journal of History Culture and Art Research, 2017)
This study investigates effects of environmental graphics on the museum's interior architecture. Organizing the interior of museums through the arrangement of elements in the space helps to attract more audiences as well as provides a cultural link. To reveal this connection, the study utilized a survey, which conducted by 256 visitors at the Museum of Contemporary Art in Tehran. The main issue of this study is: what is the first effect of environmental graphics on the museum's interior architecture? And what features of environmental graphics make museum interior architecture more attractive? The findings of the research were that the museum's interior architecture by interior environmental graphics make an integrating into the vertical movement of the visual elements with the horizontal arrangement of the visual elements in space, and the features of arranging the museum's interior architecture included an appropriate combination of contrasting spaces, harmonious relationships between space and light, and the artworks and dynamics of the horizontal arrangement of visual elements in space. Finally, it can be concluded that the museum's interior architecture creates a cultural connection and attraction by integrating the vertical movement of the visual elements with the horizontal arrangement of the visual elements in space.